1976
DOI: 10.1136/jcp.29.8.749
|View full text |Cite
|
Sign up to set email alerts
|

Assay of gentamicin in cerebrospinal fluid.

Abstract: CSF gentamicin level of 1-2 mg/l (range 0 2-2 9) after intramuscular administration of 1-5-2-5 mg/kg. The same authors measured 2-6 mg gentamicin/l (range 2.5-2.7) in CSF 24 hours after an intrathecal dose of 0 5 mg, and 15-8 mg/l (range 4 3-60) after an intraventricular dose of 0 5-1 mg. CSF levels of gentamicin up to 7 mg/l were obtained by Newman and Holt (1967) after 1-2 mg/kg per day intramuscularly and 0 2-1 mg/day intraventricularly.It is well documented that the action of gentamicin is particularly sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
2
Order By: Relevance
“…The results of our studies indicate that this is valid for gentamicin as well as for four newer aminoglycosides and that the use of distilled water or electrolyte solutions may lead to considerable inaccuracies. The reasons for the lack of agreement of our results with those of Deacon (1976a) are unclear. Technical differences such as the use of a single assay plate for all samples in our study versus the use of several separate plates by Deacon (1976a) may be responsible.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The results of our studies indicate that this is valid for gentamicin as well as for four newer aminoglycosides and that the use of distilled water or electrolyte solutions may lead to considerable inaccuracies. The reasons for the lack of agreement of our results with those of Deacon (1976a) are unclear. Technical differences such as the use of a single assay plate for all samples in our study versus the use of several separate plates by Deacon (1976a) may be responsible.…”
Section: Discussioncontrasting
confidence: 66%
“…The reasons for the lack of agreement of our results with those of Deacon (1976a) are unclear. Technical differences such as the use of a single assay plate for all samples in our study versus the use of several separate plates by Deacon (1976a) may be responsible. Shanson and Daniels (1975) reported that ionic content affected serum standards when the pH was altered from 7.5 to 6-7.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations